PENYUSUNAN PROGRAM DESA BERDASARKAN PEMETAAN SOSIAL (SOCIAL MAPPING) DI KECAMATAN PENAJAM-KABUPATEN PASER UTARA - Syahrani . (Jurnal Paradigma (JP), 2017)
Social mappingis very important in achieving goals od a particular program. With social mapping we can find social, economy and cultural conditions of a society and also about the social problems, needs and the potentiality of a society. What kind of program assigned and designed to address such things must be based on social mapping as a fundamental platform to identify problems, needs and potentiality of any society.